Boosting Water Splitting Performance of BiVO4 Photoanode through Selective Surface Decoration of Ag2S. Issue 21 (24th September 2018) - Guan, Peng; Bai, Hongye; Wang, Fagen; Yu, Hao; Xu, Dongbo; Chen, Biyi; Xia, Teng; Fan, Weiqiang; Shi, Weidong
Abstract: The unsatisfactory of solar absorption and charge separation is the main loss limiting the conversion efficiency in photoelectrochemical water splitting system. Here, Ag2 S/BiVO4 heterostructure have been fabricated for the first time to PEC splitting water, achieving efficient solar‐to‐chemical energy conversion. The Ag2 S nanoparticles evenly distributing on the surface of BiVO4 not only promotes the charge separation, but also greatly facilitates the surface hole injection. The results show that the optimal Ag2 S/BiVO4 heterostructure reach a remarkable photocurrent density of 1.91 mA/cm 2 at 1.23 V (vs RHE) under 100 mW/cm 2 irradiation, which is approximately 3.2‐fold higher than that of bare BiVO4 . The incident photon‐to‐current efficiency (IPCE) of Ag2 S/BiVO4 heterostructure have been enhanced up to 23 % in visible region ( V bias =1.23 V, 460 nm). In addition, Ag2 S/BiVO4 shows the attracting stability during photoelectrochemical process, since its photocurrent density can keep for 92 % after 2 h. The charges transfer mechanism for Ag2 S/BiVO4 heterostructure were also proposed. This work provides a new insight for constructing efficient and stable photoanodes based on BiVO4 . Abstract : Here comes the sun ! The configuration of Ag2 S/BiVO4 integrated critical components of solar absorption and charge separation for efficient photoelectrochemical water splitting.